Cyberspace is what states make of it: The social construction (and deconstruction) of strategic concepts. Issue 1 (2nd January 2023) - Whyte, Christopher
Abstract: Why do some strategic concepts come to dominate over alternative, often-entrenched views of warfighting? And what determines the staying power and proneness to change over time of the prevailing vision? Focusing on cyberspace, I describe the Internet as an artifact interpreted differently by competing interest groups. I show that reconciliation of these interpretations comes from individuals with the position and motivation to make technology work for a specific vision of use and spread that vision to other parts of the organization. By tracing the role of such key network nodes in the evolution of strategic concepts, I show that information technologies themselves act to break down barriers to engagement between social sub-elements of complex organization, making the whole susceptible to narrow parochial change. Moreover, I illustrate how the cyberspace concept is both impermanent and an attempt at problem redefinition leading to an ill-fitting lens, rather than simply a rhetorical-institutional reorientation.